Manajemen Pembelajaran Dan Memotifasi Belajar Siswa Dalam Pembelajaran Aktif Learning by Doing Di Tingkat Pendidikan Sekolah Dasar - Manjari Dewi, Wayan Kesi (Metta : Jurnal Ilmu Multidisiplin, 2022)
All know that motivating is a very important thing, it is a way to grow a sense of trust, a sense of enthusiasm and of course provide better encouragement. Learning management is a tactic or strategy in the planning and evaluation system in the education system, motivating is a very important thing, a way to grow self-confidence, enthusiasm and of course provide better encouragement. So with student motivation it can be easier to understand the material and also increase the sense of intention to learn in students. It is important to remember that every child in the class needs to be accepted by a teacher and his friends and his existence needs to be acknowledged. Increasing self-confidence, each child accepts their strengths and weaknesses, this will automatically increase their self-confidence so that their learning motivation will increase. It is very necessary to apply learning by doing learning in education because this method provides many benefits for students, one of which is providing motivation to be more independent and brave in doing various things and of course brave in being responsible for various things. Learning by doing is a learning method. which focuses on the direct experience that students will gain during the learning process. Students are encouraged to actively participate in every learning activity both physically and spiritually. The learning by doing method is very effective in influencing changes in students. Learning by doing has several forms and also teaching, namely a) student motivation b) students must play an active role c) teaching with the absence of individual differences d) feedback in teaching e) transfer f) logical arrangement of understanding.